'To correct, punish and praise' LRC leaders experiences and expressions of non-heterosexuality in Namibian schools. Issue 12 (2nd December 2017) - Francis, Dennis; Brown, Anthony
ABSTRACT: Learner representative councils (LRCs) have been constituted to foster democratic participation and citizenry in Namibian schools. Drawing on a larger UNESCO project that focused on gender violence and schooling, we report on focus group interviews with LRC members in schools in Windhoek. Working with how heterosexuality is normalised and constituted as dominant in schools, we explore how LRCs in Namibian schools respond to and confront non-heterosexuality. The findings show broader societal heterosexism and heteronormativity reflected in the attitudes and responses of the LRC leaders who draw on heteronormative discourses to regulate, silence and rehabilitate non-heterosexuality. Invoking Foucault's use of pleasure, our article provides insights for how the role of the LRC can be broadened to create socially just and inclusive schooling for lesbian, gay, bisexual and transgender youth.